Performance evaluation and monitoring of the tunnel excavation with a Mobile Tunnel Borer. Issue 1 (August 2021) - Di Giulio, A; Sebastiani, D; Cinelli, M; Ginanneschi, R; Zanetto, G; Antonelli, A; Leone, C
Abstract: The use of Tunnel Boring Machines (TBM) for tunnel excavation is widespread around the world for its capabilities and great advantages against the traditional tunnel excavation method, but sometimes this technology can be difficult to manage, requiring huge spaces for the assembly on the job site and involving complex installations at the tail of the machine. Aiming at creating a versatile and compact tunnel borer, TunnelPro and Master Drilling designed the MTB (Mobile Tunnel Borer) that is built on crawlers, easy and fast to assembly with no need of special equipment. This prototype MTB is currently excavating a Platinum mine in South Africa, being tested in very hard rocks. The study here presented, carried out by GEEG srl, startup of Sapienza University of Rome, compares the actual values of thrust, torque, penetration and cutter wear recorded during the trial excavation monitoring with those estimated with models commonly used in TBM performance prediction. The aims of this study, still ongoing, are a better comprehension of the MTB operation in terms of efficiency, work of the excavation tools, load distribution, and the evaluation of the adequacy of the most known methods when applied to this prototype machine.